Neocolonial epidemiology: Public health practice and the right to health in Guatemala (Medicine Anthropology Theory, 2019)
The relationship between public health practice and the fulfilment of the right to health is often assumed to be synergistic. With the goal of understanding how exactly this relationship happens, I studied the everyday practice of epidemiology in Guatemala, seeking to understand how it shapes and is shaped by the notion of health as a human right. Here I present findings from my ethnographic investigation of the Guatemalan Centro Nacional de Epidemiología (National Epidemiology Center), created in 2004 with the explicit mission of contributing to fulfilling the right to health for the inhabitants of Guatemala. While the relationship between epidemiological practice and the right to health is influenced by the specific configuration of local and transnational flows (bureaucratic, economic, ideological, political, scientific, social, and symbolic), epidemiologists also play an important mediating role. There are four intermediate social mechanisms that shape the relevance of epidemiological practice to fulfilling the right to health in Guatemala. Given how the country’s economic and social inequalities translate into enormous health inequities, an epidemiological practice committed to the right to health should aspire to transform, rather than reproduce, the social hierarchies underlying such inequalities. The mechanisms I identified shape how epidemiological practice contributes to the reproduction or transformation of such hierarchies. These mechanisms shape what I call ‘neocolonial epidemiology’, and include: institutional chaos, disciplinary conformism, global health international relations, and social relations at the national level.